Propagation of waves above a plage as observed by IRIS and SDO - Kayshap P.; Srivastava A.K.; Tiwari S.K.; Jelínek P.; Mathioudakis M. (My University, 2025)
Context. Magnetohydrodynamic waves are proposed as the mechanism that transport sufficient energy from the photosphere to heat the transition region (TR) and corona. However, various aspects of these waves, such as their nature, propagation characteristics, and role in the atmospheric heating process, remain poorly understood and require further investigation. Aims. We aim to investigate wave propagation within an active-region plage using IRIS and AIA observations. The main motivation is to understand the relationship between photospheric and TR oscillations. We identify the locations in the plage region where magnetic flux tubes are essentially vertical, and further we discuss the propagation and nature of these waves. Methods. We used photospheric observations from AIA (i.e., AIA 1700 Å) as well as TR imaging observations (IRIS SJI Si IV 1400.0 Å). We investigated the propagation of the waves into the TR from the photosphere using wavelet analysis (e.g., cross power, coherence, and phase difference) with the inclusion of a customized noise model. Results. A fast Fourier transform algorithm shows the distribution of wave power at photospheric and TR heights. Waves with periods between 2.0 and 9.0 min appear to be correlated between the photosphere and TR. We exploited a customized noise model to estimate the 95% confidence levels for the IRIS observations. On the basis of the sound speed in the TR and estimated propagation speed, these waves are best interpreted as slow magneto acoustic waves (SMAWs). It is found that almost all locations show correlation and propagation of waves over a broad range of periods from the photosphere to the TR. Our observations suggest that the SMAWs spatial occurrence frequency is stronly correlated between the photosphere and transition region within plage areas. © ESO 2020.